Identificação, filogenia e biodegradação de plástico LDPE por fungos lignícolas isolados do Bosque do INPA (Basidiomycota Ascomycota - Roessing, Daniel Saraiva (2023)
This dissertation describes a study that aimed to isolate and identify ligninolytic fungi from the Bosque da Ciência of the National Institute of Amazonian Research (INPA), located in Manaus, Amazonas, Brazil, and to evaluate their capacity for degrading low-density polyethylene (LDPE) films in agar medium and liquid medium. Thirty-eight samples of sporomes of ligninolytic macrofungi associated with decomposing lignocellulosic samples were collected. From these samples, eight fungi were isolated, four belonging to the phylum Basidiomycota and four to the phylum Ascomycota, with the latter four being contaminants of Basidiomycota. Phylogenetic analysis based on the ITS region sequence revealed precise identification of the isolated species, which were identified as Schizophyllum commune, Irpex laceratus, Phlebiopsis flavidoalba, Peniophora crassitunicata, Endomelanconiopsis endophytica, Annulohypoxylon stygium, Xylaria heliscus, and Xylaria plebeja. Regarding the results of LDPE film degradation assessment, all isolates showed potential in plastic degradation, depending on the culture conditions. In mineral agar medium, after 21 days of stationary culture at room temperature, all isolates except Xylaria plebeja XPM090323 promoted plastic mass reduction, with the most effective being Pleurotus ostreatus CPOINPA1, used as positive control (3.7%), Irpex laceratus ILM050722 (3%), Endomelanconiopsis endophytica EEM140223 (3.2%), and Annulohypoxylon stygium ASS170223 (3.8%). E. endophytica EEM140223 exhibited the highest laccase activity (18.1 U/Kg), while Schizophyllum commune SCM050722 excelled in peroxidase activity (5.9 U/Kg). In contrast, in liquid mineral broth, after 21 days of stationary culture at room temperature, X. plebeja XPM090323 stood out as the most efficient in reducing LDPE mass (1.5%). Finally, the isolate Xylaria heliscus XHS310123 presented the highest biomass production (4.1 g/L) and peroxidase activity (13.3 U/L), while S. commune SCM050722 showed the highest laccase activity (25.2 U/L). This study contributes to the understanding of the diversity of ligninolytic fungi in the Amazon region and their capacity for polyethylene degradation, presenting potential relevance in environmental applications and plastic waste remediation